Suppletion of numerals ‘one’ and ‘two’ in Mandarin Chinese - Wu, D (Springer, 2024)
In many languages numerals may appear in different forms depending on the context, which Greenberg (1978) called the contextual and absolute forms respectively. Greenberg made the universal generalization that if a numeral has two forms, then all the lower numerals also do. He then mentioned Mandarin Chinese as an exception because while its numeral ‘2’ has two forms, he thinks that the lower numeral ‘1’ doesn’t. This paper argues for a different view about Mandarin ‘1’–that is, ‘1’ actually has two forms just like ‘2’, despite their segmental identity. Then I argue that the two forms of ‘1’ and ‘2’ are not distinguished by use as Greenberg claimed for ‘2’, but rather by the morphophonological context: the contextual form appears when followed by overt material at the point of vocabulary insertion of the numeral, otherwise the absolute form appears. This generalization, together with the key assumption that vocabulary insertion proceeds bottom-up, leads to a particular structure for enumerating numerals like liǎng gè nv̌hái ‘two girls’, where the Cardinal head liǎng ‘two’ takes the Classifier Phrase gè nv̌hái as its complement. This paper also provides novel evidence suggesting that in Mandarin a complex enumerating numeral like ‘125 pears’ merges the complex cardinal phrase ‘125’ with the Classifier Phrase, supporting He (2015) and challenging Ionin & Matushansky (2016, 2018).